The Asymptotic Dimension of the First Grigorchuk Group Is Infinity - Smith, Justin (Revista Matemática Complutense, 2007)
We describe a sufficient condition for a finitely generated group to have infinite asymptotic dimension. As an application, we conclude that the first Grigorchuk group has infinite asymptotic dimension.